(untitled) (Indian Journal of Public Health Research & Development, 2020)
Necrotising soft-tissue infections can be defined as infections of any of the layers within the soft tissue compartment that are associated with necrotising changes. NSTI is an uncommon but life-threatening. To resolve this, some authors have developed different diagnostic adjuncts such as finger tests, skin biopsies, bedside ultrasounds and laboratory parameters in distinguishing NSTI from other soft-tissue infections (LRINEC laboratory risk indicator for necrotizing fasciitis score). Material and Method : An observational study was conducted in 50 patients (clinically diagnosed necrotising soft tissue infection). clinical observations supported by relevant investigations were documented on the attached proforma and the data so obtained was statistically analysed. Observation and result : The results suggested that maximum number of affected individuals are males, middle aged individuals. Majority of patients had normal pulse with mean body temperature of 37.3°C, normal blood pressure,INR, normal serum level of sodium, potassium and bilirubin. High level of RBS (more than 200mg/dl). Tenderness was the most commonly elicited clinical sign of NSTI, crepitus was noted in only 20% patients. Maximum number of patients were found to be infected by streptococcus pyogenes (42%). The mean level was -hemoglobin -10.2+2.3 g/dl, WBC -13,340 + 6116 /mm3, serum creatinine value of s 1.6mg/l. High discrepancy noted in value of CRP. High prevalence of NSTI involving the extremities ranging from 64.39% to 93.The mean value of LRINEC score is 6±2.92 36 % of patients having <6 score and 64% patients having score >6. Conclusion : It can be concluded that the local clinical findings are of paramount importance rather than clinical features of systemic toxicity such as fever and tachycardia.